Correction of Vertical Smile Discrepancy through Ceramic Laminate Veneers and Surgical Crown Lengthening - Paula Bernardon; Carlos Estevão Lagustera; Luiz Roberto Coutinho Manhães Junior; Bruno de Castro Figuêiredo; Danielle Shima Luize; Rolando Plumer Pezzini; George Borja de Freitas; José Luiz Cintra Junqueira (Hindawi Limited, 2019)
In cases where malocclusion is associated with intrinsic discoloration and/or discrepancies in tooth size and shape, such as peg-shaped laterals, orthodontics alone may not improve the aesthetics. In these situations, veneers may be considered as an adjunct to orthodontic treatment to improve the overall aesthetics. The aim of this study is to report a clinical case where an uneven occlusal plane was corrected, and the positioning of gingival zeniths, color, shape, and size of the dental elements involved were improved by means of gingivectomy and rehabilitation with 10 ceramic laminate veneers. It was possible to conclude that multidisciplinary treatment, when properly planned and indicated, respecting the limits and established techniques of periodontics, prosthesis, and dentistry, makes small occlusal leveling predictable and possible through these tools.